Toward sustainable grinding using minimum quantity lubrication technique with diluted oil and simultaneous wheel cleaning. (July 2020) - Sato, B.K.; Lopes, J.C.; Diniz, A.E.; Rodrigues, A.R.; de Mello, H.J.; Sanchez, L.E.A.; Aguiar, P.R.; Bianchi, E.C.
Abstract: Minimum Quantity of Lubricant (MQL) has been used in the grinding process to make the process eco-friendlier. On the other hand, it brings some technical problems to this process: the clogging phenomenon, i.e., chips adherence on the wheel cutting surface. Although this phenomenon yields widely known negative effects on productivity and workpiece quality, few studies exist about clogging in MQL grinding. Thus, this paper aims to explain the clogging formation and evaluate its effects on workpiece finishing and geometrical tolerances. External cylindrical plunge grinding tests in quenched and tempered AISI 4340 steel with CBN wheel, varying lubri-cooling conditions were carried out. Clogging affects the cutting ability of the grinding wheel and impacts on the chip formation. The addition of water in the MQL flow reduced the clogging occurrence in 40%, which corroborated to a reduction of 51% the surface roughness and 58% the roundness error. Highlights: Grinding process of AISI 4340 using CBN wheel under MQL assisted with wheel cleaning system and water dilution. Analyze of clogging phenomenon occurrence, its causes and its consequences in grinding results. Verify the influence of the percentage of water in cutting fluid on the clogging occurrence.